PERAN SERTA PERGURUAN TINGGI (PENDIDIKAN HUKUM) DALAM MEWUJUDKAN AGENDA PEMBINAAN HUKUM KHUSUSNYA DI BIDANG PERUNDANG-UNDANGAN - Seto Cahyono (Perspektif, 2004)
Thinking of college role (law department) in realizing law guidance agenda is probably obsolete and has long been constructed but it does not mean meaningless of it is ex pressed nowadays. In fact, law guidance does not pay attention on thinking or role or community as a whole. Therefore, the paper leads obsolete thinking and put some modification on it and expects it would be useful for law sector and law department.